Multidrug resistance among persons with tuberculosis in California, 1994-2003 - Granich, Reuben M; Oh, Peter; Lewis, Bryan; Porco, Travis C; Flood, Jennifer (JAMA : the journal of the American Medical Association, 2005)
Between 1994 and 2003, tuberculosis (TB) cases in California declined 33% (4834 to 3224). However, in 2003 California reported the largest number of cases in the nation, and over the past decade the proportion of cases with multidrug-resistant tuberculosis (MDR-TB) has not decreased. To describe the magnitude, trends, geographic distribution, clinical characteristics, risk factors, and outcomes of MDR-TB cases reported to the California registry of Reports of Verified Cases of TB. DESIGN, SETTING, AND CASES: Analysis of 38,291 TB cases reported from all 61 local health jurisdictions in California during 1994-2003. Multidrug-resistant TB was defined as resistance to at least isoniazid and rifampin. Results of univariate and multivariable analyses of MDR-TB magnitude, trends, geographic distribution, clinical characteristics, associated factors, and outcomes. Of 38,291 reported TB cases, 28,712 (75%) were tested for resistance to at least isoniazid and rifampin; of these, 407 MDR-TB cases (1.4%) were reported from 38 of 61 California health jurisdictions (62%); the proportion of MDR-TB cases did not significantly change over the study period (P = .87). Cases of MDR-TB were twice as likely to have cavitary lesions compared with non-MDR-TB cases (P<.001) and were 7 times more likely to have reported previous treatment for TB (P<.001). Of MDR-TB cases with outcomes, 231 (67%) completed therapy, and those with MDR-TB were significantly less likely to complete therapy than those without MDR-TB (P<.001). Multivariate analysis identified previous TB diagnosis, positive acid-fast bacilli sputum smear results, Asian/Pacific Islander ethnicity, time in the United States less than 5 years at the time of diagnosis, and outcomes of "died" and "moved" as factors associated with MDR-TB. Multidrug-resistant TB, an airborne disease with limited, costly treatment options, persists in 1% to 2% of all cases despite California's control efforts. Local and global TB control efforts are needed to prevent the further development and spread of MDR-TB.